2018
DOI: 10.1186/s12986-018-0275-x
|View full text |Cite
|
Sign up to set email alerts
|

Anti-obesity and Hypolipidemic effects of garlic oil and onion oil in rats fed a high-fat diet

Abstract: BackgroundUntil now, little research concerning the lipid-lowering and anti-obesity functions of garlic oil and onion oil has been performed. The objective of this study was to explore the effects of garlic oil and onion oil on serum lipid levels in hyperlipidemia model rats, to provide a scientific basis for the prevention of hyperlipidemia through a dietary approach, and to explore the potential health benefits of garlic and onion.MethodNinety-six male Sprague-Dawley rats were randomly allocated into eight g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(64 citation statements)
references
References 31 publications
2
60
2
Order By: Relevance
“…The animals in the high-fat diet group were considered obese when their body weight was 10% higher than the weight of animals in the control group. 18,19 Treatment Urolithin A and B (97% purity) were purchased from BLD Pharma, China. After the 10 weeks of feeding, animals in group 3 HFDA (HFD + Uro-A) and group 4 HFDB (HFD + Uro-B) were given an intraperitoneal (I.P.)…”
Section: Animalsmentioning
confidence: 99%
“…The animals in the high-fat diet group were considered obese when their body weight was 10% higher than the weight of animals in the control group. 18,19 Treatment Urolithin A and B (97% purity) were purchased from BLD Pharma, China. After the 10 weeks of feeding, animals in group 3 HFDA (HFD + Uro-A) and group 4 HFDB (HFD + Uro-B) were given an intraperitoneal (I.P.)…”
Section: Animalsmentioning
confidence: 99%
“…DATS majorly involved in the activation of the ERK pathway and negatively regulate the adipogenic transcription factor expression during adipogenesis. These findings together suggested that garlic and its compounds could effectively reduce obesity by regulating the adipogenesis process [ 71 ].…”
Section: Biological Activities Of Sulfur Compounds From mentioning
confidence: 99%
“…It is important to provide fluffy bread in a fermentation process [18]. Garlic has several functional compounds such as flavonoids and antioxidants [19]. In this study, it was suggested that some ingredients of garlic increased the fermentation ability of yeast.…”
Section: Characterization Of Seaweed Breadmentioning
confidence: 93%